Spatial movement as a resistance strategy in a holocaust novel A Blessing on the Moon - Sri Sumaryani (Universitas Islam Sultan Agung, 2021)
Exploring Jewish resistance in relation to the Holocaust has become one major topic widely discussed in the Holocaust novels written by the second or third generations of Holocaust survivors. The fact that these writers primarily have no direct experience with the event somewhat shows that the paramount effects of the tragedy expand generations and leave trauma that lingers. To cope with the narration of atrocities, resistance strategy is often employed by the Holocaust writers and to a certain point has a function to represent the struggle of the survivors. Joseph Skibell as the third-generation writer deploys a strategy of spatial movement as a coping mechanism and resistance against atrocities in his magical realist novel A Blessing on the Moon. Using Sara Upstone’s spatial politics perspective, this research aims to investigate the spatial movement performed by the main character and to explain how it produces the resistance strategy. In doing so, it will also further examine the scale and characteristics of various spatial locations used in the novel as a means of resistance. As it goes along, the issue of trauma and identity of the Holocaust survivors and their descendants is also explained.